Predominant role of antioxidants in ameliorating the oxidative stress induced by pesticides. Issue 2 (17th February 2021) - Medithi, Srujana; Jonnalagadda, Padmaja R.; Jee, Babban
Abstract: Oxidative stress has been reported as one of the adverse effects caused due to pesticides, which is the main mechanism of the toxicity in humans and animals and is a useful parameter in monitoring studies. It involves an imbalance in the equilibrium state of ROS and antioxidant defenses leading to alterations in various antioxidant enzyme levels and lipid peroxidation. The objective of the current paper is to present a review of the potential role and protective mechanism action of the antioxidant micronutrient supplementation to ameliorate the oxidative stress induced by pesticides. Studies in animal models and human were retrieved through the relevant search of the literature and categorized. Various animal studies were categorized according to the type of supplementation. Animal studies provide evidence to conclude the potential protective role of antioxidants in ameliorating the adverse effects of pesticides. Similar studies in humans are meager suggesting for further comprehensive research.